Hospital operations improving communication skills - HSTN (Health & Sciences Television Network) (Carrollton : HSTN, 1998)
Part 1 of this set discusses strategies for improving communication with co-workers. Part 2 shows how miscommunication can undermine job productivity and performance. Part 3 stresses the importance of attentive listening
Keywords: Hospital Administration; Hospital Communication System